Melatonin and Renal Protection: Novel Perspectives from Animal Experiments and Human Studies (Review) - Hrenak, Jaroslav; Paulis, Ludovit; Repova, Kristina; Aziriova, Silvia; J. Nagtegaal, Elsbeth; J. Reiter, Russel; Simko, Fedor (Current Pharmaceutical Design, 2015)
Chronic kidney disease (CKD) is a serious public health problem. Current therapies are designed to slow down progression of the disease and avoid the necessity of dialysis or kidney transplantation. CKD is characterized by chronic inflammation and progressive cell death resulting in fibrotic rebuilding of renal tissue. Melatonin, the primary product of the pineal gland, has been shown to have pluripotent protective effects in many organs and tissues. It exerts anti-hypertensive, anti-inflammatory, anti-apoptotic, and antiremodelling actions. A principal mechanism of these numerous melatonin benefits resides in its extraordinary high efficacy as an antioxidant and scavenger protecting cells both extracellularly and in all subcellular structures. In addition to these receptor-independent actions, the effects of melatonin via specific MT-receptors may be beneficial. In several animal models of CKD, involving experimental hypertension, diabetes mellitus and various models of nephrotoxicity, melatonin reduced the oxidative burden, attenuated the chronic inflammation and limited apoptosis. These effects were associated with the reduction of proteinuria, damage of parenchymal cells and fibrosis. In humans, melatonin’s chronobiological action attenuates sleep disturbances in hemodialyzed patients suffering from a relative melatonin deficiency. Moreover, melatonin reduces the oxidative burden and improves iron metabolism in hemodialyzed patients. In conclusion, the pleiotropic physiological actions of melatonin induce beneficial effects at numerous pathophysiological levels related to CKD both under experimental and clinical conditions. It is hoped that this review will prompt a large clinical trial to determine the efficacy of this nontoxic indoleamine as a potential treatment for this debilitating disease.
Keywords: melatonin